Digital Transformation in Higher Education Accreditation: Streamlining Self-Evaluation Workflows at Polytechnic Institutions - Pinem, Sanjaya; Tyas, Sari Setyaning; Indera Nata Raharja (Cattleya Darmaya Fortuna, 2025)
In the landscape of vocational higher education, accreditation is the benchmark for institutional quality and public accountability. However, many institutions, particularly polytechnics, struggle with the administrative burden of manual compliance, characterized by fragmented data and inefficient